The Effectiveness of The Problem-Solving Strategy in Improving Students’ Speaking Skills - Hilal, Alda Alfiana; Atmowardoyo, Haryanto; Aeni, Nur (Journal of Excellence in English Language Education, 2025)
This research was conducted to find out the effectiveness of the problem-solving strategy in improving students’ speaking skills at SMP Negeri 4 Sungguminasa. The research design used a pre-experimental quantitative method. This research was conducted at SMP Negeri 4 Sungguminasa with a population of 311 students from class IX and a sample of 31 students selected from class IX-D, which was taken by simple random sampling. The results showed that the null hypothesis (H0), which states that the problem-solving strategy does not significantly improve students' English-speaking skills, is rejected. In contrast, the alternative hypothesis (H1), which states that the problem-solving strategy significantly improves students' English-speaking skills, is accepted. From this statement, it can be summarized that the problem-solving strategy has significantly improved students’ English-speaking skills. This improvement was seen in five main components: vocabulary, pronunciation, fluency, and comprehension when presenting arguments.